Stentless Strategy by Drug-Coated Balloon Angioplasty following Directional Coronary Atherectomy for Left Main Bifurcation Lesion - Norihiro Kobayashi; Masahiro Yamawaki; Shinsuke Mori; Masakazu Tsutsumi; Yohsuke Honda; Kenji Makino; Shigemitsu Shirai; Masafumi Mizusawa; Yoshiaki Ito (Journal of Interventional Cardiology)
Aims. We aimed to evaluate the efficacy of stentless strategy by drug-coated balloon (DCB) angioplasty following directional coronary atherectomy (DCA) for left main (LM) bifurcation lesions. Methods. A total of 38 patients who underwent DCB angioplasty following DCA for LM bifurcation lesions were retrospectively enrolled. The primary endpoint was target vessel failure (TVF) at 12 months. Secondary endpoints included procedure-related major events during the hospitalization, major adverse cardiac events at 12 months, ischemia-driven target lesion revascularization (TLR) at 12 months, and bleeding complications defined as the Bleeding Academic Research Consortium criteria ≥2 at 12 months. Results. Among these 38 lesions, 31 lesions were de novo LM bifurcation lesions and 7 lesions were stent edge restenosis at the left anterior descending (LAD) ostium. The mean % plaque area (%PA) after DCA was 44.0 ± 7.4%. TVF at 12 months occurred in 1 lesion (3.2%) of de novo LM bifurcation lesion and in 3 lesions (42.9%) of stent edge restenosis at the LAD ostium. All events of TVF were ischemia-driven TLR by percutaneous coronary intervention. Among 4 TLR cases, %PA after DCA was high (55.9%) in the de novo LM bifurcation lesions; on the other hand, %PA after DCA was low (42.4%, 38.7%, and 25.7% in the 3 cases) in stent edge restenosis at the LAD ostium. No procedure-related major events were observed during hospitalization. There was no cardiac death, no myocardial infarction, no coronary artery bypass grafting, and no bleeding complications at 12 months. Conclusions. Stentless strategy by DCB angioplasty following DCA for de novo LM bifurcation lesions resulted in acceptable outcomes. On the other hand, its efficacy was limited for stent edge restenosis at the LAD ostium even after aggressive debulking by DCA.